Highly stable and efficient cathode-buffer-layer-free inverted perovskite solar cells. Issue 11 (12th March 2021) - Kim, Yong Ryun; Oh, Chang Mok; Yoon, Chang Jae; Kim, Ju-Hyeon; Park, Kiyoung; Lee, Kwanghee; Hwang, In-Wook; Kim, Heejoo
Abstract : We proposed a novel simplified device structure for efficient and stable inverted perovskite solar cells that has no cathode buffer layer by modifying the electron transport layer with insulating polymers as an additive. Abstract : A simpler and less expensive fabrication process is one of the essential demands for the commercialization of perovskite solar cells (PeSCs). Especially, inverted PeSCs (I-PeSCs) require a cathode buffer layer (CBL) for fabricating highly efficient and stable PeSCs. However, this increases the number of fabrication step. Here, we demonstrate highly stable and efficient cathode-buffer-layer-free I-PeSCs via additive engineering on an ETL, which is based on phenyl-C61 -butyric acid methyl ester (PC61 BM) with a small amount of poly(methyl methacrylate) (PMMA). This modified ETL shows not only a simplified fabrication process but also effective extraction of charge from the perovskite to a high work function copper electrode (Cu) by formation of an interfacial dipole at the interfaces between the ETL and the Cu. Additionally, it exhibits good passivation of the trap density existing along the grain boundaries and surface of the perovskite layer, reducing the non-radiative recombination and consistent with the increases in open-circuit voltage ( V oc ). As a result, I-PeSCs with a blend PC61 BM : PMMA ETL demonstrate an enhancement in the power conversion efficiency (PCE) from 13.55% (without PMMA) to 18.38%. Furthermore, they exhibit both burn-in-free behaviour in photostability measurements by maximum power-point tracking (MPPT) method and long-term air-stability (30 days for T90 ) in ambient air. Lastly, we obtained PCE of 15.03% and 16.83% for large-area (1 cm 2 ) I-PeSCs with PC61 BM and PC61 BM : PMMA, respectively. This method provides an alternative route to reduce the fabrication time and budget for commercialization of I-PeSCs without sacrificing device performance.